Influence of Lenslet Configuration on Short-Term Visual Performance in Myopia Control Spectacle Lenses - Li, Xue; Ding, Chenglu; Li, Yuhao; Lim, Ee Woon; Gao, Yi; Fermigier, Bruno; Yang, Adeline; Chen, Hao; Bao, Jinhua (Frontiers in Neuroscience, 2021)
Purpose. To evaluate short-term visual performance and optical quality of 3 different lenslets configuration on myopia control spectacle lenses. Methods. A cross-over design study. Distance visual acuity (VA) was measured in 50 myopic children; contrast sensitivity (CS) was measured in 36 myopic children. For each test, four spectacle lenses were evaluated in random order: single vision lens (SVL), lens with concentric rings of highly aspherical lenslets (HAL), lens with concentric rings of slightly aspherical lenslets (SAL) and lens with honeycomb configuration of spherical lenslets (HC). The modulation transfer function (MTF) and MTF area (MTFa) were used to determine the optical quality. All tests were performed monocularly on the right eye with full correction. Results. HAL and SAL had larger MTFa than HC. VA in lenses with lenslets was significantly reduced compared to SVL (all p < 0.01). The reduction in VA was worse with HC than with SAL (p = 0.02) and HAL (p = 0.03); no effect of lenslets asphericity was found (p > 0.05). VA changes induced by lenslets did not show any correlation with spherical equivalent refraction (all p > 0.05) but had a weak positive association with age for SAL (r = 0.36, p = 0.01) and HC (r = 0.31, p = 0.03), but not for HAL (p = 0.30). The area under the log contrast sensitivity function (AULCSF) decreased with HAL and HC (all p<0.001) in all illumination levels, and AULCSF with HAL were higher than with HC in photopic condition (1.17 ± 0.10 vs 1.10 ± 0.13, p = 0.0004). The presence of lenslets did not affect CS at 3 cpd (p = 0.80). At 6 to 18 cpd, CS was significantly reduced by HAL and HC (all p<0.05), not by SAL (p>0.05) compared to SVL. At high spatial frequencies (>12 cpd) both SAL and HAL reduced CS significantly less than HC (all p<0.01). Conclusions. Short-term visual performance was minimally impaired by looking through the lenslets structure of myopia control spectacle lenses. Concentric rings with aspherical lenslets had a significantly lower impact on both VA and CS than honeycomb configuration with spherical lenslets.